Tendency to Democracy and Study of the Social Elements Related to the Issue; Case Study Citizens of Tehran - Mohammad Hossein Panahi (Faṣlnāmah-i Pizhūhish/hā-yi Rāhburdī-i Siyāsat, 2015)
This study has investigated the effects of social factors on tendency towards democracy. Data for this analysis were collected from a sample of 643 citizens of Tehran aged 20 years and older. The theoretical framework was formulated using theories of Bourdiou, Inglehart, Habermas and Giddens. Social factors included social class, cultural capital, media usage, and religiosity. Descriptive findings reveal that majority of the Tehrani citizens have low tendency towards democracy. Only 4 percent of them have high level of tendency towards democracy. These citizens were more democratic in their attitudes than in their conducts. Explanatory findings show that there is significant relation among various dimensions of social class (i.e., cultural capital, economic capital and social status) with the tendency towards democracy. In addition, there is also significant correlation between cultural factors (i.e., social tolerance, social participation, democratic attitudes towards family) with the tendency towards democracy. Findings demonstrated that cultural capital was the most significant predictor of the dependent variable